AVALIAÇÃO DA REPRODUTIBILIDADE DE PONTOS CEFALOMÉTRICOS NAS TELERRADIOGRAFIAS DIGITAIS EM NORMA LATERAL NOS FORMATOS DICOM, TIFF E JPEG - Falcão, Livia Maria Rocha (2009)
The digital radiography image acquired by the photostimulable storage phosphor plates system normally is showed in the computer screen as a DICOM format, characterized for the high resolution of the images. As this format uses a lot of memory space for storage, the digital images are submitted to a compression, which optimizes the capacity of space on the computers and reduces the time of transmission for the Internet. The aim of this study was to evaluate the effect of TIFF and JPEG compression in the intraobserver and interobserver reproducibility of the cephalometric landmarks identification on lateral headfilms compared with DICOM format. The sample consisted of 90 digital lateral cephalometric images obtained from 30 individuals, in DICOM format. These images were converted for formats JPEG, with Quality Factor 80 and TIFF. After blind and random the sample, three observers, orthodontists, were calibrated and ask to identify 15 cephalometric landmarks in each image using x and y coordinates system. The results had shown that the cephalometric landmarks identification had presented agreement of intraobserver and interobserver reproducibility, except for the points Go, Po, Or, B and Pog'. The statistic analyze showed no difference between the file formats for each point and axis. JPEG and TIFF compressions studied had not effect in the intraobserver and interobserver reproducibility of the cephalometric landmarks identification on digital lateral headfilm.(AU)